Cyclicity of motivation as a factor in control staff in innovative organizations - I. V. Mandritsa; T. A. Doroshewskya (Вестник Северо-Кавказского федерального университета)
The article is devoted to questions of recurrence of motivation in human resource management of the innovative organizations and to theoretical researches of the nature of its phenomenon and studying for improvement of techniques of stimulation and motivation of the personnel.